De vita brevi necnon arte longa Raphaëlis Schaurek - Benke, József (Díké - A Márkus Dezső Összehasonlító Jogtörténeti Kutatócsoport folyóirata, 2020)
This contribution pays tribute to the memory of István Kajtár, a renowned Legal Historian of the Faculty of Law of Pécs. On this occasion, the paper examines the life and the legal and non-legal work of Raphael Schaurek, the first Professor of Private Law (1923–1950) in the Hungarian Royal Elizabeth University of Pécs Faculty of Law. The essay shows that Schaurek’s life and work embodied the truth of the Hippocratic Aphorisms’ opening sentence, according to which “ho bios brakhýs, hē de tekhnē makrē” (i.e. ‘life is short, and art long’). The adage came true in the longevity of the intrinsic professor’s effects towards the disciples and their disciples. The dedication of this contribution points a parallelism: The mentioned proverb of Hippocrates prevailed in the life and work also of Professor István Kajtár, whose legacy of vocation and euergetism survives in the generations of his students.